Cervical Cancer Screening among HIV‑Positive Women in Urban Uganda: A Cross Sectional Study - Najjuka, Sarah Maria; Olwit, Connie; Kaggwa, Mark Mohan; Nabirye, Rose Chalo; Ngabirano, Tom Denis (BMC Women's Health, 2022)
Women living with Human Immunodeficiency Virus (HIV) are at a high risk for early development of cervical cancer. Adherence to cervical cancer prevention strategies in this population is vital for the early detection and treatment of cervical cancer. This study aimed to determine the prevalence and factors associated with cervical cancer screening among HIV-positive women attending an urban HIV care center in Uganda.This cross-sectional study included 205 HIV-positive women receiving care at an urban HIV care center. An interviewer-administered questionnaire was used to capture sociodemographic information, history of screening for cervical cancer, and reproductive health characteristics. Logistic regression analysis was used to determine the factors associated with cervical cancer screening.Of the 205 HIV-positive women with a mean age of 37.5 ± 8.87 that participated in the study, majority (n = 201, 98%) were aware of cervical cancer screening. Ninety participants (44%) had ever been screened for cervical cancer and only 33 (16.1%) had been screened in the past year. Obtaining information about cancer of the cervix and cervical cancer screening from health care professionals was significantly associated with higher levels of cervical cancer screening (adjusted odds ratio = 5.61, 95% confidence interval: 2.50–12.61, p value < 0.001).This study highlights the low prevalence of cervical cancer screening among HIV-positive women and underscores the role of health professionals as an effective source of information on cervical cancer and cervical cancer screening. Patient education programs in HIV prevention and care facilities should emphasize cervical cancer screening messages to enhance the uptake of screening services.
Keywords: Cervical cancer, Cervical cancer screening, HIV, Women, Health professionals, Uganda